Discovery of novel ascorbic acid derivatives and other metabolites in fruit of Rosa roxburghii Tratt through untargeted metabolomics and feature-based molecular networking. (30th March 2023) - Zhang, Yaqi; Bian, Xiqing; Yan, Guanyu; Sun, Baoqing; Miao, Wen; Huang, Mingzheng; Li, Na; Wu, Jian-Lin
Highlights: 251 metabolites were identified in FRR based on untargeted metabolomics. 4 novel flavonoids were identified in FRR through untargeted LC-MS approach. 3 ascorbyl hexosides were quantified in FRR and FRS for the first time. 17 novel AA derivatives were discovered in FRR based on FBMN analysis. The correlation of biofunctions and metabolites between FRR and FRS were analyzed. Abstract: Fruit of Rosa roxburghii Tratt (FRR) is widely used in functional food industry while short of metabolites research. Herein, we firstly identified 251 metabolites in FRR based on untargeted liquid chromatography-mass spectrometry (LC-MS) approach. Then, 42 differential compounds were sought out to avoid the confusing use of FRR and fruit of R. sterilis S. D. Shi (FRS), and FRR was evaluated exhibiting higher biofunction potential. Moreover, a quantitative LC-MS approach was established to determine the contents of 3 ascorbyl hexosides, and FRR with higher contents should be better source than FRS. Additionally, 17 ascorbic acid (AA) derivatives formed by conjugation of ascorbyl unit with organic acids, flavonoids, or glucuronic acid were also discovered in FRR through characteristic ions of AA and feature-based molecular networking (FBMN), enlightening that AA derivatives were not limited to ascorbyl glycosides. This study provided abundant metabolites information of FRR, laying the basis for exploitation of FRR.